2012
DOI: 10.1186/1476-4598-11-87
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β promotes stemness and invasiveness of colon cancer cells through Zeb1 activation

Abstract: BackgroundIL-1β is a pleiotropic pro-inflammatory cytokine and its up-regulation is closely associated with various cancers including gastrointestinal tumors. However, it remains unclear how IL-1β may contribute to the initiation and development of these inflammation-associated cancers. Here we investigated the role of IL-1β in colon cancer stem cell (CSC) development.MethodsUsing self-renewal assay, soft-agar assay, invasion assay, real-time PCR analysis, immunoblot assay and shRNA knockdown, we determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
219
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(230 citation statements)
references
References 48 publications
10
219
0
1
Order By: Relevance
“…The above observation is consistent with other data that report that the transgenic overexpression of IL1β in gastric mucosa is sufficient to induce gastric cancer in mice [35]. New findings have recently indicated that IL1β may promote colon tumor growth and invasion via the activation of cancer stem cell self-renewal and epithelial-mesenchymal transition (EMT) [36] As expected, the second most dysregulated canonical pathway in adenocarcinoma was the Wnt/β-catenin pathway. Wnt target genes are varied and context-specific [37] because Wnt/β-catenin signaling controls proliferation, cell fate determination and differentiation in numerous developmental stages and in adult tissue homeostasis.…”
Section: Discussionsupporting
confidence: 80%
“…The above observation is consistent with other data that report that the transgenic overexpression of IL1β in gastric mucosa is sufficient to induce gastric cancer in mice [35]. New findings have recently indicated that IL1β may promote colon tumor growth and invasion via the activation of cancer stem cell self-renewal and epithelial-mesenchymal transition (EMT) [36] As expected, the second most dysregulated canonical pathway in adenocarcinoma was the Wnt/β-catenin pathway. Wnt target genes are varied and context-specific [37] because Wnt/β-catenin signaling controls proliferation, cell fate determination and differentiation in numerous developmental stages and in adult tissue homeostasis.…”
Section: Discussionsupporting
confidence: 80%
“…IL‐1β promotes colon cancer cell stemness and invasiveness (Li et al ., 2012). IL‐8 is also associated with cancer stem cell‐like properties, and its expression correlates with poor prognosis in human pancreatic cancer (Chen et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b promotes EMT and cancer cell stemness in a number of cell types. 8,9 Cell typeespecific studies on the importance of the inflammasome for cancers with an inflammatory signature have indicated that the inflammasome is a key player in the etiology of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition to promoting fibrosis, IL-1b induces epithelial to mesenchymal transition (EMT) in corneal endothelial cells and induces stemness in colon cancer cells through the activation of transcription factors that regulate the mesenchymal phenotype. 8,9 On the other hand, NLRP3 and apoptosis speck-like protein containing a CARD domain (ASC) (an adaptor protein for the assembly of the inflammasome) both play a role in transforming growth factor (TGF)-b signaling independent of their inflammasome activity in tubular epithelial cells. 10 We therefore hypothesized that the NLRP3 inflammasome and its products facilitate mesothelial to fibroblastic transition (MFT) of HMCs in response to asbestos exposure.…”
mentioning
confidence: 99%